2020
DOI: 10.1002/hbm.24984
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of the frontotemporal network in preattentive detection of abstract changes: Perturbs and observes with transcranial magnetic stimulation and event‐related optical signal

Abstract: Current theories of automatic or preattentive change detection suggest a regularity or prediction violation mechanism involving functional connectivity between the inferior frontal cortex (IFC) and the superior temporal cortex (STC). By disrupting the IFC function with transcranial magnetic stimulation (TMS) and recording the later STC mismatch response with event‐related optical signal (EROS), previous study demonstrated a causal IFC‐to‐STC functional connection in detecting a pitch or physical change. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Due to the preattentive nature, the detection of deviance could only be reflected by the MMN or the corresponding mismatch brain responses, but not behavioral measures. Our TMS-optical imaging studies [25,26] showed that single pulse TMS on the right IFC 80 ms after deviant onset abolished the STC mismatch response at 150-200 ms, when the deviant was preceded by 4-7 standards. However, the STC mismatch response was preserved when deviant was preceded by a longer standard train [25].…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Due to the preattentive nature, the detection of deviance could only be reflected by the MMN or the corresponding mismatch brain responses, but not behavioral measures. Our TMS-optical imaging studies [25,26] showed that single pulse TMS on the right IFC 80 ms after deviant onset abolished the STC mismatch response at 150-200 ms, when the deviant was preceded by 4-7 standards. However, the STC mismatch response was preserved when deviant was preceded by a longer standard train [25].…”
Section: Introductionmentioning
confidence: 77%
“…In the Auditory Control block, the TMS coil was positioned near the right IFC but Stimulation intensity was set at 80% of the resting motor threshold (rMT), which has demonstrated an inhibitory effect on the brain responses in previous studies [40]. Similar to our previous studies [25,26], rMT was determined by using the 5-centimeter rule (see was determined based on previous TMS-EROS [25,26] and EROS studies [15][16][17][18]41]. The exact IFC location for each individual was obtained by first transforming the individual MRI scan from native space to Talairach space to obtain the transformation matrix, then reverse transforming the IFC location from Talairach space back to native space of each participant using the software AFNI [42].…”
Section: J O U R N a L P R E -P R O O F ------------Insert Figure 1 Amentioning
confidence: 92%
See 3 more Smart Citations